2017
DOI: 10.1007/s00122-017-2963-8
|View full text |Cite
|
Sign up to set email alerts
|

Development of 25 near-isogenic lines (NILs) with ten BPH resistance genes in rice (Oryza sativa L.): production, resistance spectrum, and molecular analysis

Abstract: A first set of 25 NILs carrying ten BPH resistance genes and their pyramids was developed in the background of indica variety IR24 for insect resistance breeding in rice. Brown planthopper (Nilaparvata lugens Stal.) is one of the most destructive insect pests in rice. Development of near-isogenic lines (NILs) is an important strategy for genetic analysis of brown planthopper (BPH) resistance (R) genes and their deployment against diverse BPH populations. A set of 25 NILs with 9 single R genes and 16 multiple R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
64
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 49 publications
3
64
0
1
Order By: Relevance
“…For example, Yasuda et al (2015) reported rice lines with pairs of blast resistance genes to be only comparable to lines with a single gene which may have a stronger suppressive effect. Similarly, pyramiding of brown planthopper (BPH) resistance genes in a susceptible variety IR24 markedly improved BPH resistance against four BPH populations in the Philippines than the single BPH introgressed lines (Jena et al 2017). In our previous study of bakanae disease resistance (Lee et al 2018) revealed that the gene pyramided lines harboring qBK1 WD + qBK1 had a much higher level of resistance than those possessing either qBK1 WD or qBK1.…”
Section: Discussionmentioning
confidence: 96%
“…For example, Yasuda et al (2015) reported rice lines with pairs of blast resistance genes to be only comparable to lines with a single gene which may have a stronger suppressive effect. Similarly, pyramiding of brown planthopper (BPH) resistance genes in a susceptible variety IR24 markedly improved BPH resistance against four BPH populations in the Philippines than the single BPH introgressed lines (Jena et al 2017). In our previous study of bakanae disease resistance (Lee et al 2018) revealed that the gene pyramided lines harboring qBK1 WD + qBK1 had a much higher level of resistance than those possessing either qBK1 WD or qBK1.…”
Section: Discussionmentioning
confidence: 96%
“…In fact, NILs always present extensive residual heterozygosity because of the complexity of genomic composition and recombination [ 32 , 33 ]. Moreover, previous studies in which SNP chips were used have generally reported the presence of SNPs between NILs [ 34 36 ]. Compared to SNP chips, next-generation sequencing has a broader and more sensitive detection ability, which might also explain why we detected more SNPs than did previous researchers.…”
Section: Discussionmentioning
confidence: 99%
“…New rice varieties with BPH resistance have been developed and introduced to farmers [1]. The BPH32 gene is still used in rice breeding programs [20], and the functional DNA markers of this gene have been developed for MAS [21].…”
Section: Discussionmentioning
confidence: 99%
“…Before and after BPH infestation, the average expression level of BPH32 constantly remained high in the leaf sheath tissue indicating that the gene function may not be induced by the BPH infestation. [21]. The NILs will be useful as new genetic resources for BPH resistance breeding.…”
Section: Discussionmentioning
confidence: 99%